Mathematical modeling of wildland fire initiation and spread. (March 2020) - Agranat, Vladimir; Perminov, Valeriy
Abstract: The aim of this paper is to create a user-friendly computational tool for analysis of wildland fire behavior and its effect on urban and other structures. A physics-based multiphase Computational Fluid Dynamics (CFD) model of wildfire initiation and spread has been developed and incorporated into the multi-purpose CFD software, PHOENICS. It accounts for all the important physicochemical processes: drying, pyrolysis, char combustion, turbulent combustion of gaseous products of pyrolysis, exchange of mass, momentum and energy between gas and solid phase, turbulent flow and convective, conductive and radiative heat transfer. Turbulence is modeled by using a RNG k-ε model and the radiative heat transfer is represented by the IMMERSOL model. The Arrhenius-type kinetics are used for heterogeneous reactions and the eddy-breakup approach is applied for gaseous combustion. The model has been validated using the experimental data. Highlights: A multiphase wildfire model has been developed and incorporated into the PHOENICS CFD software. The model accounts for drying, pyrolysis, char combustion, turbulent gaseous combustion and convective, conductive and radiative heat transfer. The mathematical model was validated using the experimental data.